Hospital mergers can impact the offer of health care services - Daniel Herrera-Araujo; Joanna Piechucka (DIW Weekly Report, 2021)
In the last decades, many European hospital markets witnessed a wave of mergers leading to increased levels of market concentration. The effects of hospital mergers and the effectiveness of competition enforcement have been discussed by politicians but understudied by academics. This report studies how hospital mergers impact hospital service provision by focusing on the French hospital industry from 2009 to 2017. The report finds that local mergers may result in a change in the health care services offered. For example, merging hospitals reduce the offer of duplicate services. The results suggest that competition authorities may want to encompass these strategic reactions in their analysis when deciding ex ante whether or not to approve mergers. These insights are also particularly relevant for the German hospital industry, which operates in a similar regulatory context to the French case.
Keywords: C23; I11; L40; 330; mergers; industry concentration; hospital industry